Influence of Sugars and Surface Properties on Wettability and Adhesion of Starch-Based Model Suspensions on Polytetrafluoroethylene (PTFE) and Polyethylene Terephthalate (PET) Surfaces - Ana Caroline Frabetti; Jaqueline Oliveira de Moraes; Vanessa Jury; Lionel Boillereaux; João Borges Laurindo (Foods, 2025)
In food drying processes such as cast-tape drying, refractance window, and drum drying, spreading food suspensions on hydrophobic surfaces is critical. This study investigated the effects of low-molar-mass sugars (glucose, sucrose, and fructose) on the rheology and surface tension of cassava starch suspensions, which served as model systems. Wettability was assessed on hydrophobic surfaces, including new polytetrafluoroethylene (PTFE) and polyethylene terephthalate (PET) films, with additional testing on sandpaper-abraded PTFE (named PTFE R+) to evaluate the influence of surface roughness. PET film exhibited lower roughness (Ra = X µm) and higher surface tension (71 mN/m) compared to PTFE (surface tension 65 mN/m). Contact angles on PET (93–124°) were significantly higher than on PTFE (89–113°), indicating greater product adhesion on PET. All suspensions showed pseudoplastic behavior, and the addition of the surfactant Tween 20 slightly reduced surface tension (by ≈1–5 mN/m) but did not significantly enhance wettability. Sucrose and fructose increased wettability on PTFE R+, but the effects of the sugar varied depending on the surface. These findings suggest that PTFE surfaces reduce product sticking during drying compared to PET. Interactions between sugars, Tween 20, and hydrophobic surfaces must be considered to optimize spreading and reduce product sticking during drying. This knowledge can guide improvements in drying processes for food products.